NONAN GaitPrint: An IMU gait database of healthy older adults - Tyler M. Wiles; Seung Kyeom Kim; Madhur Mangalam; Joel H. Sommerfeld; Kolby J. Brink; Alli Grunkemeyer; Marilena Kalaitzi Manifrenti; Anaelle E. Charles; Narges Shakerian; Mehrnoush Haghighatnejad; Spyridon Mastorakis; Nick Stergiou; et al. (Scientific Data)
Abstract The continued effort to study gait kinematics and the increased interest in identifying individuals based on their gait patterns could be strengthened by the inclusion of data from older groups. To address this need and complement our previous database on healthy young adults, we present an addition to the Nonlinear Analysis Core (NONAN) GaitPrint database. We offer full-body inertial measurement data during self-paced overground walking on a 200 m indoor track of 41 older adults (56 + years old; 20 men and 21 women; age: 64.7 ± 7.5 years; height: 1.7 ± 0.1 m; body mass: 81.1 ± 17.8 kg) across 18 four-minute trials conducted over two days. The multiple recordings are supported by a range of pre-calculated spatiotemporal variables, a list of each subject’s anthropometrics, notes for each walking trial, and template scripts for easier application of our data to classroom assignments or laboratory research. In addition, a preliminary Bayesian analysis found a range of evidence supporting age-related gait changes between this database and our database on young adults.